A percepção dos stakeholders locais sobre os impactos econômicos, sociais e ambientais de pequenas centrais hidrelétricas - Pagnussatt, Daiane (2016)
Renewable energy sources have a large potential to contribute to the sustainable development of specific territories by providing them with a wide variety of socioeconomic benefits, including, enhanced regional development opportunities, new corporation’s attraction and employment and income generation. At the same time, the implementation of renewable energy projects brings impacts on national level, but especially in locally where they operate. Del Río e Burguillo (2009) argues that most studies on renewable energy socioeconomic benefits has usually been too general (for example, in national level), and a focus on the regional and especially the local level has been lacking. This analysis becomes especially important once the economic, environmental and energy impacts determine (in part) whether the completed project is accepted (or not). If a project is not accepted by local stakeholders, it may not be implemented. The objective of this study is to analyze local stakeholder’s perceptions, particularly residents and authorities, of small hydropower plants impacts, in the social, environmental and economic dimensions. Q methodology was explored as a tool to analyze the diversity of local stakeholders’ perspectives. This work has identified five perspectives: “environmental concern”, “regional development”, “infrastructure availability”, “socioeconomic relation” and “economic and environmental relation”. The existence of five different perspectives related to the analyzed small hydropower plant impacts calls attention of managers and politicians for transparence and communication improvement related on the use of a public asset, the river. This study also clarifies local stakeholder’s role on promoting the increase of potential benefits, especially social and economic, generated by small hydropower plants, through their local articulation, mainly previously to environmental licensing phase, in order to discuss all regional demands.